Estudo da paisagem da Floresta Nacional de São Francisco de Paula, RS, Brasil - Teixeira, Italo Filippi (2005)
The importance of Brazilian landscapes and the destruction problem are already known. Despite, the worry expressed by the population with the landscapes destination is normally emotional and subjective. The manifestations over the gardening beauty don t help to elaborate and to choose management alternatives. More objective concepts are necessary. But, the world worry about valuable landscapes disappearance resulted in new techniques for the gardening resources development. In these techniques, principles well worked before are used in gardening and gardening architecture. For the first time, we are trying to quantify and compare the landscape variables. The National Forest of São Francisco de Paula (FLONA), belonging to Brazilian Government and under responsibility of Environment Brazilian Institute (IBAMA), is located in Rincão dos Kröeff district, São Francisco de Paula county, RS. It takes part from the micro-region Campos de Cima da Serra, in the border of Planalto, transition zone between Floresta Ombrófila Densa and Floresta Ombrófila Mista (Forest with Araucaria), one of the 11 (eleven) physiographic micro-region from Rio Grande do Sul state. FLONA is located between the geographic coordinates 29° 23 and 29° 28 of south latitude and 50° 23 and 50° 25 of west longitude, in Serra Gaúcha, north-east region from the state, at an average altitude of 930 m. The study had as objective to identify and quantify the physical environment and human activities characteristics that compose each visual unit; to interpret and value the vivacity measure from each visual element in its unit; to analyze the visual sequence of these dynamic effect of these units and plan the landscapes dynamic to ecotourism at FLONA. As sample unit, it was used a hexagon, with 200 m of ray, distributed in a hexagonal mesh, elaborated through Campeiro 1.0. Program. This mesh with 158 hexagons was overlapped over the land use card, building maps and land marks, insulation map and altimetric map, obtained from the visual interpretation and digitalization in screen image from Sensor Ikronos II, with multi-spectral composition and 4m. resolution, using IDRISI 32 Program. The hexagons were evaluated at laboratory and at the field, through 22 variables, with a scale from 1 to 5. The result generated a data matrix, used in SPSS Program, where Cluster and Discriminant analyzes were done to determine the hexagons groups to form landscapes. Through hexagons valuation the vivacity of each one was also determined. As result, 5 landscapes called Araucaria, native, hillside, transition and exotic were obtained. The native landscape showed 100% from its hexagons in a high level of vivacity, characterizing as the most pictorial from FLONA. Five scenic routs or roads were determined to ecotourism, scientific tourism or environment education use. It is possible to conclude that the variables which impacted the subjectivity and perception were the ones that most influenced due to valoration. The vivacity is located (gardening and scenic potential) in the valley of Rolante river region, basically concentrated in Native and hillside landscape and to visualize the pictorial elements, the visitors should visit the area from 11 a.m. to 1 p. m, using Route 5.